A qualitative study of teleworking in Malaysia: perceptual factors affecting the millennials during Covid-19 - Ong, Si Kai (2022)
Different generations have different values and preferences. This study investigates Malaysian Millennial employees’ perceptions towards teleworking during the coronavirus (COVID-19) situation, with those working in small and medium enterprises (SMEs) in Klang Valley (KV) as the research context. The interviews yielded 10 responses, wherein 6 factors – work, personal life, organisation, environment, culture and technology – were discovered through literature review and template analysis (TA). These are the perceptual factors that have a very or somewhat negative effect on Millennials’ teleworking experiences if they are not given thought to. As when the analysis was moving forward, instead of influencing teleworking perception directly, these factors are causing impacts on Millennials’ job performance (JP) and person-environment (P-E) fit – the two indicators that have stronger capacities, in turn, stipulate Millennials’ teleworking perceptions. The findings suggested the importance of embracing social exchange since a greater knowledge of what drives employees’ intentions to telework is necessary for employers to reap the well-researched benefits, meanwhile, to minimise the potential drawbacks.